2016
DOI: 10.4209/aaqr.2015.11.0632
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO, O3, and SO2 Measurements at the Summit of Mt. Fuji during the Summer of 2013

Abstract: Atmospheric trace gases CO, O 3 , and SO 2 were observed at the summit of Mt. Fuji (3776 m a.s.l.) during the summer of 2013. Considerable variations were observed in the concentrations of CO and O 3 ; however, they were correlated in most cases. Trends analyzed through backward trajectory calculations showed lower concentrations of CO and O 3 transported from the Pacific Ocean and South East Asia directions, while higher concentrations were detected from the direction of the Asian continent. High O 3 and low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The most common indicatory air pollutant in summer was O 3 , but, in winter, it was PM 2.5 . Previous studies have shown that atmospheric relative humidity is negatively correlated with O 3 concentration and that a lower relative humidity is conducive to the formation of O 3 (Kato et al, 2016;Li et al, 2017b;Gong et al, 2018). In summer, low relative humidity and high temperatures and wind speeds are conducive to the dispersion, diffusion, and dilution of air pollutants.…”
Section: The Top Five Days With the Highest Aqis From 2017 To 2019mentioning
confidence: 98%
“…The most common indicatory air pollutant in summer was O 3 , but, in winter, it was PM 2.5 . Previous studies have shown that atmospheric relative humidity is negatively correlated with O 3 concentration and that a lower relative humidity is conducive to the formation of O 3 (Kato et al, 2016;Li et al, 2017b;Gong et al, 2018). In summer, low relative humidity and high temperatures and wind speeds are conducive to the dispersion, diffusion, and dilution of air pollutants.…”
Section: The Top Five Days With the Highest Aqis From 2017 To 2019mentioning
confidence: 98%
“…The trip intensity and daily concentration of PM 10 from January 12 to March 27, 2019 and those in 2020 during the same period in Shenzhen, Guangzhou, and Foshan, respectively. world's largest coal producer and consumer (Kurokawa et al, 2013;Kato et al, 2016). It can be seen that SO 2 concentrations in Guangzhou and Foshan from January 12 to March 26 in 2020 were reduced, indicating that factory shutdowns caused by the Chinese New Year holiday and epidemic prevention actions led to significant reductions in SO 2 emissions.…”
Section: So2 Concentrationmentioning
confidence: 99%
“…It is critical to ensure more accurate representation of BVOC emissions within air quality simulations, as this could alter regimes of ambient ozone formation and the relative importance of controls on anthropogenic NO X and VOC emissions [36,37]. However, better representation of BVOC emissions in Japan is not a single solution for eliminating overestimation of its ambient ozone concentrations, as these are greatly influenced by ozone transport from the continent, particularly during summer 2013 [38]. Therefore, it is necessary to find other ways to reduce simulated ambient ozone concentrations at the larger regional scale.…”
Section: Discussionmentioning
confidence: 99%